PENGARUH KOMPETENSI SUMBERDAYA MANUSIA DAN PEMANFAAT TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL INTERVENING - -, Endarwati; Pahlevi, Reza Widhar; Putri, Ajeng Kharisma; Dwiarti, Rina (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study investigates impact of Human Resource (HR) Competence and the utilization of Information Technology (IT) on the quality financial reports, with the Internal Control System (ICS) serving as a mediating variable. The case study was conducted on Baitul Maal wat Tamwil (BMT) institutions in the Yogyakarta region. Using a quantitative approach, data were collected through questionnaires distributed to BMT accounting and management staff from June to July 2025. The study population included all BMTs in Yogyakarta, and the sample was determined using a purposive sampling method based on predefined criteria. Data analysis was performed with the help of SPSS software, including descriptive, validity, and reliability tests, as well as path analysis to test the proposed hypotheses. The findings of this study indicate that HR competence and IT utilization have a positive and significant effect on the quality of financial reports. Furthermore, the ICS was proven to effectively mediate the relationship between HR competence, IT utilization, and the quality of financial reports.